2017
DOI: 10.1038/srep46462
|View full text |Cite
|
Sign up to set email alerts
|

Anchored but not internalized: shape dependent endocytosis of nanodiamond

Abstract: Nanoparticle-cell interactions begin with the cellular uptake of the nanoparticles, a process that eventually determines their cellular fate. In the present work, we show that the morphological features of nanodiamonds (NDs) affect both the anchoring and internalization stages of their endocytosis. While a prickly ND (with sharp edges/corners) has no trouble of anchoring onto the plasma membrane, it suffers from difficult internalization afterwards. In comparison, the internalization of a round ND (obtained by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 47 publications
2
22
0
Order By: Relevance
“…Anisotropic gold nanoparticles with different shapes exhibited significant different cellular uptake (Xie et al, 2017). Similar results were also reported on other inorganic nanoparticles (Karaman et al, 2012;Dai et al, 2015), carbon nanotubes (Smith et al, 2012;Zhang et al, 2017), polymeric nanoparticles (Jurney et al, 2017), and folate nanocarriers (Tahmasbi Rad et al, 2019). Consistent with these findings, our result showed that LNSs obtained significantly enhanced cellular uptake and in vivo tumor extravasation ability compared with their spherical controls which shared the same length of lipid backbone.…”
Section: Discussionsupporting
confidence: 89%
“…Anisotropic gold nanoparticles with different shapes exhibited significant different cellular uptake (Xie et al, 2017). Similar results were also reported on other inorganic nanoparticles (Karaman et al, 2012;Dai et al, 2015), carbon nanotubes (Smith et al, 2012;Zhang et al, 2017), polymeric nanoparticles (Jurney et al, 2017), and folate nanocarriers (Tahmasbi Rad et al, 2019). Consistent with these findings, our result showed that LNSs obtained significantly enhanced cellular uptake and in vivo tumor extravasation ability compared with their spherical controls which shared the same length of lipid backbone.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, the smallest, isolated particles were observed to be free in the cytoplasm, when the bigger particles and aggregates were localized in the intracellular endocytic vesicles. Besides, the shape of a HPHT diamond nanoparticle appears to affect its internalization, trafficking inside the cell, and excretion from it [ 19 , 20 ]. Nevertheless, such behaviors are still debated in the scientific community.…”
Section: Cellular Processes Sensingmentioning
confidence: 99%
“…They explained that the curve shape of spherical particles allowed a limited number of their binding sites to interact with target cell receptors while the elongated nanoparticles had higher surface area, which facilitated the multivalent interaction of these particles with cell surface. Similarly, Zhang et al 109 mentioned that the prickly nanoparticles had a higher anchoring amount compared with the round nanoparticles. The results could be understood as originating from the contact surface area difference of the two types of nanoparticles with the plasma membrane.…”
Section: Effects Of Nanoparticle Morphology On Cellular Uptake In Vivmentioning
confidence: 95%
“…Endocytosis has two stages: adhesion and internalization. 109 The shape of nanoparticles has a significant impact on the cell adhesion of a wide variety of nanoparticles. Salatin et al 110 mentioned that the elongated nanoparticles showed higher efficiency in adhering to the cells rather than the spherical nanoparticles.…”
Section: Effects Of Nanoparticle Morphology On Cellular Uptake In Vivmentioning
confidence: 99%